2002
DOI: 10.1254/jjp.88.123
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Enzymes Comprising the Polyol Pathway in Various Rat Tissues Determined by the Competitive RT-PCR Method

Abstract: ABSTRACT-The quantitative measurements of aldose reductase (AR) and sorbitol dehydrogenase (SDH) gene expression in various rat tissues were performed by the competitive reverse transcription-polymerase chain reaction (RT-PCR). AR mRNA was detectable in all tissues analyzed with pronounced differences in the amounts. SDH mRNA was most abundant in testes and liver, but was absent from lens. The estimation of the AR cDNA / SDH cDNA ratio showed that the relative abundance of SDH to AR differs among tissues. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Otherwise, the finding of a similar decrease in sorbitol levels in nerve and lens with ranirestat administration for 21 days (Table 2) indicates potent AR inhibition without organ specificity. Others have reported that AR mRNA is widely distributed in organs that are affected by high levels of hyperglycemia, such as the lens, retina, and peripheral nerve (1). Consequently, to the extent that the polyol pathway contributes to the underlying pathophysiological cascade leading to the microvascular complications of diabetes, it may be predicted that ranirestat might prove effective in treating those microvascular complications, that is, retinopathy, nephropathy, and polyneuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the finding of a similar decrease in sorbitol levels in nerve and lens with ranirestat administration for 21 days (Table 2) indicates potent AR inhibition without organ specificity. Others have reported that AR mRNA is widely distributed in organs that are affected by high levels of hyperglycemia, such as the lens, retina, and peripheral nerve (1). Consequently, to the extent that the polyol pathway contributes to the underlying pathophysiological cascade leading to the microvascular complications of diabetes, it may be predicted that ranirestat might prove effective in treating those microvascular complications, that is, retinopathy, nephropathy, and polyneuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…1). AR is widely distributed throughout the body, including the target organs that are affected by diabetes mellitus such as the lens, retina, kidney (1), and peripheral nerves (2). Activation of the polyol pathway during hyperglycemia results in the accumulation of sorbitol in various tissues so it is believed to be a factor in the development of the complications associated with diabetes (3).…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular concentration of fructose also is elevated in those tissues of diabetic patients in which the polyol pathway is active, in particular the ocular lens, kidney, and peripheral nerves. 6,7,36 As AR has a high Km for glucose, the polyol pathway is not very active at normal glucose levels. In hyperglycemia, however, glucose levels in insulinindependent tissues, such as brain and nerve tissue, kidney, lens, and the red blood cells, increase and, consequently, there is an increase in the activity of the polyol pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The polyol pathway, an accessory of glucose metabolism, entails the conversion of glucose to fructose by aldose reductase (AR) and sorbitol dehydrogenase (SDH). [6][7][8][9] So far, most studies have been focused on non-enzymatic glycation (also called the Maillard reaction) by glucose, because glucose is by far the most abundant sugar in blood.…”
mentioning
confidence: 99%
“…In pathway (1) under hyperglycemic conditions a rise in the intracellular glucose concentration stimulates the production of fructose via the polyol pathway in insulin-independent tissues, such as nerve tissue, the kidneys, the lens of the eye, red blood cells, and the brain [39][40][41][42] . In addition, fructose is a constituent of sucrose and high-fructose corn syrup (HFCS), and hence, is included in many people's diets [43,44] .…”
Section: Pathway For the In Vivo Synthesis Of Glycer-agesmentioning
confidence: 99%